Outcome of combined unicompartmental knee replacement and combined or sequential anterior cruciate ligament reconstruction: a study of 52 cases with mean follow-up of five years. - Weston-Simons, J; Pandit, H; Jenkins, C; Jackson, W; Price, A; Gill, H; Dodd, C; Murray, D (2012)
The Oxford unicompartmental knee replacement (UKR) is an established treatment option in the management of symptomatic end-stage medial compartmental osteoarthritis (MCOA), which works well in the young and active patient. However, previous studies have shown that it is reliable only in the presence of a functionally intact anterior cruciate ligament (ACL). This review reports the outcomes, at a mean of five years and a maximum of ten years, of 52 consecutive patients with a mean age of 51 years (36 to 57) who underwent staged or simultaneous ACL reconstruction and Oxford UKR. At the last follow-up (with one patient lost to follow-up), the mean Oxford knee score was 41 (sd 6.3; 17 to 48). Two patients required conversion to TKR: one for progression of lateral compartment osteoarthritis and one for infection. Implant survival at five years was 93% (95% CI 83 to 100). All but one patient reported being satisfied with the procedure. The outcome was not significantly influenced by age, gender, femoral or tibial tunnel placement, or whether the procedure was undertaken at one- or two-stages. In summary, ACL reconstruction and Oxford UKR gives good results in patients with end-stage MCOA secondary to ACL deficiency.